The spectre of David Graeber - or of Madagascar about him. Comments on the translation issue - Falleiros, Guilherme (Cadernos de Campo (São Paulo, 1991), 2023)
Presentation by Guilherme Falleiros to the special issue David Graeber: an ethnography of authority. This special section is composed of translations of five articles translated by Leonardo Viana Braga and Renato Martinelli with the revision of Luiz Gustavo Pradella; the review by Bruno Huyer of the book "Pirate Enlightenment, or the Real Libertalia" and a photographic essay by Nika Dubrovsky.